Governance structure and the tendency to do financial statements fraud - Agung Nur Probohudono; Anju Theresia Lubis; Ertambang Nahartyo; Siti Arifah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
This study aimed to examine the influence of the governance structure which consists of the age of directors, educational background of directors, directors’ gender, managerial ownership, and the existence of Independent Board of Commissioners on financial statement fraud. This research's populations are Manufacturing, Property, Real estate, and Construction Companies listed on the Indonesia Stock Exchange (IDX) period 2014-2018. The type of data used in research was secondary data and using a purposive sampling method to determine 475 companies for the samples. This research used a logistic regression analysis. The result of this research indicated that the age of directors, the gender of directors, and managerial ownership had a significant negative effect on financial statement fraud. However, the study did not find the advantage of the educational background of directors and the existence of the independent member of the Board of Commissioners on financial statement fraud.